Hydrodynamics of gas phase in a shallow bubble column from in-line photography. (10th August 2020) - Liu, Zhen; Li, Xiangyang; Mao, Zai-Sha; Yuan, Shaojun; Yang, Chao
Highlights: Bubble area distribution is firstly used to explain the BSD more clearly. Tiny bubbles previously ignored are of significance to gas-liquid mass transfer. The radial BHD is parabolic in SBC in contrast with flat in developed region in TBC. Abstract: In shallow bubble columns (SBC), the under-developing hydrodynamics have not been well understood. The spatially-resolved measurements are conducted to probe bubble shape, size and gas holdup in SBC using a telecentric vision probe in tap water and CMC solution. More regular bubble shape and more serious polarization of bubble size are found in CMC. Bubble shape distributions agree well with the Wellek correlation and Bozzano-Dente correlation because of weaker interaction between bubbles. Different from the literature, relationship between aspect ratio and Eotvos number does depend on sampling locations. Too many tiny bubbles detected interfere with the observation of the conventional bubble size distribution. Assisted by the bubble area distributions, the actual effects of small and large bubbles on gas-liquid mass transfer are clarified. Higher volume fraction of the plume zone in SBC leads to the parabolic BHD in contrast to the almost flat profiles in the developed flow in TBC.